PENGARUH ARUS EKSITASI TERHADAP ARUS STATOR MOTOR SINKRON 3 FASA DENGAN VIRTUAL INSTRUMENT - Carmanto, Anto; Gunawan, Wawan (Universitas Lampung, 2023)
The three-phase current value of a synchronous motor has a great impact on its long-term reliability and performance under load. Therefore, maintenance and monitoring must be performed to determine the performance of synchronous motors. A virtual instrument and its LabView software can be used as a method to determine the operating current value of a synchronous motor. The device used in the study contains a synchronous motor as a load, and his LabView-equipped controller is used to execute commands during synchronous motor testing. NI MyDAQ is used as an input to the controller prior to using LabView, so it can be customized for use as an input to motors and controllers. Power is supplied by adjusting the motor input voltage to 380 volts and the controller input voltage to 220 volts. The purpose of the research is to develop tools and simulation software for synchronous motors that use voltage regulators to react to variations and determine minimum and maximum voltage values to determine motor performance. As a result of examination, the motor output reached a maximum current value of 0.4A at idle and a maximum controller current value.